Fe+Cl2=FeCl2
FeCl2+2 NaOH=Fe(OH)2↓+2 NaCl
Fe(OH)2=FeO+H2O
FeO+H2=Fe+H2O
2Fe + 6H2SO4 = Fe2(SO4)3 + 3SO2↑ + 6H2O
Fe2(SO4)3 + 3Ba(OH)2 = 2Fe(OH)3↓ + 3BaSO4↓
2 Fe(OH)3=Fe2O3+3 H2O
Fe2O3+3 H2=2 Fe+3 H2O
FeCl2+2 NaOH=Fe(OH)2+2 NaCl
Fe(OH)2+...=FeO
Fe+ 6H2SO4=Fe2(SO4)3
Fe2(SO4)3+3Ba(OH)2=Fe(OH)3
Fe+Cl2=FeCl2
FeCl2+2 NaOH=Fe(OH)2↓+2 NaCl
Fe(OH)2=FeO+H2O
FeO+H2=Fe+H2O
2Fe + 6H2SO4 = Fe2(SO4)3 + 3SO2↑ + 6H2O
Fe2(SO4)3 + 3Ba(OH)2 = 2Fe(OH)3↓ + 3BaSO4↓
2 Fe(OH)3=Fe2O3+3 H2O
Fe2O3+3 H2=2 Fe+3 H2O
Fe+Cl2=FeCl2
FeCl2+2 NaOH=Fe(OH)2+2 NaCl
Fe(OH)2+...=FeO
FeO+H2=Fe+H2O
Fe+ 6H2SO4=Fe2(SO4)3
Fe2(SO4)3+3Ba(OH)2=Fe(OH)3
2 Fe(OH)3=Fe2O3+3 H2O
Fe2O3+3 H2=2 Fe+3 H2O